Odpowiedzi

2010-02-20T11:14:03+01:00
Oblicz wartość wyrażenia x do potęgi2-2y do potęgi2+xy dla:

x^2-2y^2+xy= x(1+y) - 2y^2

a)x=2 i y=-5;

2(-4)-2*25= -8-50=-58

b)x=1/2 i y=2/3;

5/6-2*(4/9)= 5/6-8/9 = -3/54= -1/16

c)x=2 1/2 i y=1 1/4;

5/2*(9/4)-2*(1/16)= 45/8- 1/8 = 44/8= 11/2
d)x=0,3 i y=0,7;

0,3*1,7-2*0,49= 0,51-0,98= - 0,47
e)x=0,75 i y=-1/3;

0,75* (2/3) - 2/9= 1/2 - 2/9 = 9/18 - 4/18 = 5/18
  • Użytkownik Zadane
2010-02-20T11:28:59+01:00
A)x²-2y²+xy=2²-2*(-5)²+2*(-5)=4-50-10=-56

b)x²-2y²+xy=(½)²-2*(⅔)²+½*⅔=¼-⁴/₃+⅓=³/₁₂-¹⁶/₁₂+⁴/₁₂=-⁹/₁₂=-¾

c)x²-2y²+xy=(2½)²-2*(1¼)²+2½*1¼= ²⁵/₄-²⁵/₈+²⁵/₈=⁵⁰/₈-²⁵/₈+²⁵/₈= ⁵⁰/₈=6²/₈=6¼

d)x²-2y²+xy=0,3²-2*0,7²+0,3*0,7=0,09-0,98+0,21=-0,68

e)x²-2y²+xy=(¾)²-2*(-⅓)²+¾*(-⅓)=⁹/₁₆-²/₉-¼=⁸¹/₁₄₄-³²/₁₄₄-³⁶/₁₄₄= ¹³/₁₄₄